Coronavirus Disease 2019: Cardiac Complications and Considerations for Returning to Sports Participation - Daniel X Augustine (Radcliffe Medical Media, 2021)
Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2. While the majority of symptoms and morbidity relate to the lung, cardiac complications have been well reported and confer increased mortality. Many countries in Europe have passed the peak of the pandemic and adaptations are being made as we progress towards a ‘new normal’. As part of this, governments have been planning strategies for the return of elite sports. This article summarises the potential implications of COVID-19 for athletes returning to sport, including common cardiac complications of the disease; consensus recommendations for the return to sport after having COVID-19; and international recommendations for the management of cardiac pathology that may occur as a result of COVID-19. The authors also examine the potential overlap of pathology with physiological change seen in athletes’ hearts.